Financial forensics body of knowledge - Dorrell, Darrell D. (Wiley, 2012)
Financial Forensics Body of Knowledge is the unique, innovative, and definitive guide and technical reference work for the financial forensics and/or forensic accounting professional, including nearly 300 forensic tools, techniques, methods and methodologies apply to virtually all civil, criminal and dispute matters. Many of the tools have never before been published.